BCOR Expression in Mullerian Adenosarcoma: A Potential Diagnostic Pitfall. (June 2020) - Muthukumarana, Vidarshi; Fix, Daniel J.; Stolnicu, Simona; Park, Kay J.; Soslow, Robert A.; Benayed, Ryma; Ladanyi, Marc; Antonescu, Cristina R.; Chiang, Sarah
Abstract : Adenosarcoma can mimic high-grade endometrial stromal sarcoma with ZC3H7B-BCOR fusion that may show entrapped glands and often exhibits diffuse BCOR expression. We encountered diffuse BCOR expression in rare adenosarcomas and sought to define its frequency among a larger cohort of these tumors. BCOR immunohistochemistry was performed on archival formalin-fixed paraffin-embedded tumor tissue in 13 of 14 adenosarcomas with and without stromal overgrowth arising in the uterus or ovary. The staining intensity and percentage of positive tumor nuclei in the mesenchymal component were evaluated. Eleven cases with sufficient tumoral tissue were subjected to fluorescence in situ hybridization for the detection of BCOR, BCORL1, NUTM1, ZC3H7B, and JAZF1 rearrangement. Three cases were subjected to targeted RNA sequencing. BCOR was expressed in 9 of 13 (70%) tumors, including 6 with and 3 without stromal overgrowth. Moderate to strong staining in >70% of cells was seen throughout in 1 low-grade and 6 high-grade tumors, 5 of which had stromal overgrowth. No staining was seen in 3 low-grade and 1 high-grade tumors with stromal overgrowth. One tumor demonstrating extensive sex cord-like differentiation and diffuse BCOR expression harbored JAZF1 and BCORL1 rearrangements. No BCOR or BCORL1 rearrangement was identified in the remaining tumors. BCOR expression is seen in most adenosarcomas with and without stromal overgrowth. BCORL1 rearrangement is seen in rare tumors with diffuse BCOR expression. Assessment of BCOR or BCORL1 rearrangement status is required in adenosarcomas demonstrating BCOR expression.